Prediction of grinding machinability when grind P20 tool steel using TiO2 nanofluid - Lai, Woon Shyz (2012)
The surface roughness is a variable often used to describe the quality of ground surfaces as well as to evaluate the competitiveness of the overall grinding system. A grinding process was performed on the P20 tool steel by changing the grinding conditions, including the depth of cut, the grinding passes, the type of wheel, and the cutting fluid supply in the experiment. The main objective of the study is to investigate the effect of TiO2 nanofluid on the grinding surface finish and wheel tool life. The 0.1 % volume concentration of the TiO2 nanofluid is prepared as to compare the effectiveness with the water based coolant. The selected specimens undergo SEM to assess the surface integrity of the machined surfaces. ANN prediction models are developed from the collected data.The result showed the reduction of 20 % to 40 % surface roughness value in grinding with TiO2 nanofluid. As conclusion, TiO2 nanofluid exhibits the better grinding surface quality. For recommendation, various machining can be conducted using nanofluid to emphasize better results.